The association between child maltreatment and juvenile delinquency in the context of Situational Action Theory: Crime propensity and criminogenic exposure as mediators in a sample of European youth? - Doelman, Eline HJ (European journal of criminology, 2023)
The current study investigates the association between physical child maltreatment and juvenile delinquent behavior in the context of the Situational Action Theory (SAT) (Wikström, 2006, 2017, 2020). Self-control, morality and exposure to criminogenic settings are proposed as possible mechanisms explaining the association between physical child maltreatment and adolescent offending. The hypotheses are tested in a subsample of the third wave of the International Self-Report Delinquency Study (ISRD3), a large international non-clinical study on delinquency and victimization among adolescents. The final sample consists of N = 24,956 adolescents aged 12?16 years from nine West European countries. While controlling for dependence due to nested data and several covariates, the models are tested for overall offending and separately for violent and property offending. Results confirm that physical child maltreatment is associated with the main concepts of SAT (lower self-control; lower morality; and more exposure to criminogenic environments), which in turn are associated with juvenile delinquency. The models show partial mediation for overall offending, property offending and violent offending. The findings provide support for the theoretical prowess of SAT and its main concepts: self-control, morality and exposure to criminogenic settings as mediators in the well-established physical child maltreatment/delinquency link. These findings are consistent with the ?cycle of violence? perspective and contribute to the theoretical clarification of the mechanisms involved in the child maltreatment/delinquency link. The findings fail to confirm a ?crime-specific propensity?. The article concludes with a discussion of implications for prevention.